2011
DOI: 10.1007/s00464-010-1558-0
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional stomach analysis with computed tomography after laparoscopic sleeve gastrectomy: sleeve dilation and thoracic migration

Abstract: Multislice computed tomography allows for a comprehensive and quantitative evaluation of the anatomy after LSG and thus provides new insights in the process of sleeve dilation. Intrathoracic migration of the staple line could be identified as a possible cause of persistent regurgitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(52 citation statements)
references
References 27 publications
(38 reference statements)
2
46
0
4
Order By: Relevance
“…Thus, it appears useful to know the pre-and post-operative stomach volumes and to correlate it with weight loss achieved after LSG. Methods described in the literature range from intraoperative measurement by instillation of normal saline or methylene blue, UGI contrast series and MDCT [6][7][8][9][10]. In the present study, we used MDCT for estimating pre-and post-operative stomach volumes and found that MDCT correlates well with the volume of the excised stomach measured by saline distension.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Thus, it appears useful to know the pre-and post-operative stomach volumes and to correlate it with weight loss achieved after LSG. Methods described in the literature range from intraoperative measurement by instillation of normal saline or methylene blue, UGI contrast series and MDCT [6][7][8][9][10]. In the present study, we used MDCT for estimating pre-and post-operative stomach volumes and found that MDCT correlates well with the volume of the excised stomach measured by saline distension.…”
Section: Discussionmentioning
confidence: 59%
“…Among the various methods described to determine sleeve volume like infusion of saline solution or methylene blue through orogastric tube [6,7], upper gastro-intestinal contrast [8] and multidetector computed tomography (MDCT) with post image processing, the latter has shown reasonable results [9,10]. Volume measurement with MDCT has been compared previously with UGI contrast studies and has shown comparable results [10].…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Mechanisms that may induce increased GERD in patients with GERD with sleeve gastrectomy include hypotensive LES (28), blunting of the angle of His (29), decreased gastric compliance (30), delayed gastric emptying (29), reduced plasma ghrelin levels (31), gastric sleeve anatomy (32), and hiatal hernia (33). In the cohort study by Himpens et al (34), GERD occurred at a rate of 23.6% at six years after surgery.…”
Section: Sleeve Gastrectomymentioning
confidence: 99%
“…Under normal anatomic conditions, the stomach is fixed in place by four "ligaments", that is, the gastrohepatic, gastrosplenic, gastrocolic, and gastrophrenic ligaments, and laxity of these, the absence of omentum, paraesophageal hernia, or diaphragmatic eventrations increase the mobility and ability of the stomach to rotate organo-axially or mesentero-axially [14]. It has recently been reported that loss of abdominal ligament fixation along the greater curvature of the stomach may result in improper gastric pouch positioning and cause food intolerance and persistent reflux [15,16].…”
Section: Methodsmentioning
confidence: 99%